The Impact of Machine Learning Technology on E-Learning Platforms on Student Learning Behavior - Asrul Sani; Tomi Apra santosa; Ratih Dheviana Puru Hitaningtyas; Daniel Pasaribu; Yohanis Yakubun (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
This study aims to determine the influence of Machine Learning Technology on the E-Learning Platform on student learning behavior. This research is a type of meta-analysis research. The data source comes from 10 national journals indexed by SINTA published in 2022-2024. Deep collection technique through direct observation. The process of searching for virgin sources through google scholar, ERIC, and IEEE. Data analysis is statistical data analysis by calculating the effect size value with the help of the JSAP application. The results of the study concluded that the average effect size value was 0.791 in the medium effect size category. These findings explain that there is a significant influence of machine learning technology on e-learning platforms on student learning behavior.